2017
DOI: 10.1038/labinvest.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected UVR and non-UVR mutation burden in some acral and cutaneous melanomas

Abstract: Ultraviolet radiation (UVR) mutagenesis causes nearly all cutaneous melanomas, however, since UVR signatures are largely absent in acral melanoma, as well as melanoma in sun-protected sites, the cause of these melanomas is unknown. Wholegenome sequencing data generated as part of the Australian Melanoma Genome Project was supplemented with a detailed histopathological assessment with the melanomas then classified as UVR or non-UVR related, based on their mutation signatures. The clinicopathological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
(54 reference statements)
3
32
1
Order By: Relevance
“…1c ). One acral melanoma had a UV-associated mutational signature, as has also been observed by others 18 , 19 . Overall though, patients with sun-exposed primary tumors had a higher mutational load than patients with primary lesions at sites with little or no such exposure ( p < 0.001, Mann–Whitney U -test [MW]; Supplementary Figure 1a ).…”
Section: Resultssupporting
confidence: 80%
“…1c ). One acral melanoma had a UV-associated mutational signature, as has also been observed by others 18 , 19 . Overall though, patients with sun-exposed primary tumors had a higher mutational load than patients with primary lesions at sites with little or no such exposure ( p < 0.001, Mann–Whitney U -test [MW]; Supplementary Figure 1a ).…”
Section: Resultssupporting
confidence: 80%
“…NF1 mutations are detected in 14e17% of all melanomas and are associated with the highest mutation burden and strongest UV signature (Cancer Genome Atlas, 2015; Cirenajwis et al, 2017;Hayward et al, 2017). Rawson et al (2017) reported that acral melanomas with high UV signatures occur on subungual sites and harbor BRAF or NF1 mutations. In our study, of 11 patients with NF1 mutations, only one had a left thumbnail subungual melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive therapy or immunosuppressive UV radiation-related cell damage also increase the risk of melanoma [ 7 ]. In addition, adiposity, chronic inflammation, and oxidative stress have all been positively related to melanoma incidence [ 6 , 8 , 9 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation-related DNA damage is the most relevant modifiable melanoma risk factor, and oxidative stress, chronic inflammation, and impaired immune function all represent contributing factors [ 6 9 ]. In contrast, surprisingly little is known about the independent effects of physical activity and cardiorespiratory fitness on melanoma prevention, although physical exercise has a positive impact on numerous biological pathways, such as increased DNA repair capacity, decreased levels of oxidative stress, reduced inflammation, and enhanced immune function [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%